Pemberdayaan Teknologi Informasi untuk Keunggulan Bisnis - - Supriyanto (Universitas Negeri Yogyakarta, 2004)
Nowadays, IT maintenance is mostly needed by the companies, even small scale companies. It must be supported by 4 (four) factors to be a key in increasing competition power and competitive advantages for the companies. They are (1) IT management system; (2) IT storage management; (3) IT defense system and (4) Pervasive management. By the way, companies which wont maintenance the four factors will be a looser in the business competition. Thats way IT maintenance is a must for every companies to reach their competitive advantages.